ANALYSIS OF PRODUCTION PERFORMANCE AND FINANCIAL VIABILITY OF A BROILER CHICKEN FARMING BUSINESS IN A CLOSED HOUSE SYSTEM (Case Study At Ud. Pande In Pejeng Village, Tampaksiring Sub-District, Gianyar District) - M. Z. A. J., PUTRA; SUKANATA, I W.; WIRAPARTHA, M. (Majalah Ilmiah Peternakan, 2021)
This study aims to determine the performance of production, the feasibility of financial and Break Even Point of broiler chicken with the closed house system. The research starting from February 2020 until March 2020 in UD. Pande located in Pejeng Village, Tampaksiring District, Gianyar Regency. This study used primary and secondary data. Variables observed in this study is the performance of production broiler chickens include: body weight, we- ight gain, Feed Conversion Ratio (FCR), depletion and Performance Index (IP), as well as the feasibility of financial include: Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit per Cost (Net B / C), Pay Back Period (PBP) and Break Even Point (BEP). The data research analyzed with quantitative descriptive analysis. The results of the research study show that the average harvesting age of broiler chickens is 34 days, the average harvest weight 1,880 kg, the average body weight gain 1,836 kg, the average FCR 1.583, the average depletion 3,82%, the average performance index 328,81. Based on the results of financial analysis, this farm produces NPV 103,772,930, IRR 16,35%, Net B/C 1.40, Pay Back Period within 0.37 years, BEP within 9.97 years, BEP of production live chickens of 132,600 kg/year, BEP, of the price of live chickens Rp. 14.924/kg. Based on these results, it can be concluded that the broiler chickens reared with the closed house partnership system are good and feasible to run.